Ankle-brachial index as a predictor of coronary disease events in elderly patients submitted to coronary angiography (Clinics, 2013)
OBJECTIVES: To correlate the importance of the ankle-brachial index in terms of cardiovascular morbimortalityand the extent of coronary arterial disease amongst elderly patients without clinical manifestations of lowerlimb peripheral arterial disease.METHODS: We analyzed prospective data from 100 patients over 65 years of age with coronary arterial disease,as confirmed by coronary angiography, and with over 70% stenosis of at least one sub-epicardial coronaryartery. We measured the ankle-brachial index immediately after coronary angiography, and a value of ,0.9was used to diagnose peripheral arterial disease.RESULTS: The patients’ average age was 77.4 years. The most prevalent risk factor was hypertension (96%), andthe median late follow-up appointment was 28.9 months. The ankle-brachial index was ,0.9 in 47% of thepatients, and a low index was more prevalent in patients with multiarterial coronary disease compared topatients with uniarterial disease in the same group. Using a bivariate analysis, only an ankle-brachial index of,0.9 was a strong predictive factor for cardiovascular events, thereby increasing all-cause deaths and fatal andnon-fatal acute myocardial infarctions two- to three-fold.CONCLUSION: In elderly patients with documented coronary disease, a low ankle-brachial index (,0.9) wasassociated with the severity and extent of coronary arterial disease, and in late follow-up appointments, a lowindex was correlated with an increase in the occurrence of major cardiovascular events.